Largest single‐centre experience of dulaglutide for management of diabetes mellitus in solid organ transplant recipients. Issue 4 (20th January 2019) - Singh, Priyamvada; Pesavento, Todd E.; Washburn, Kenneth; Walsh, Debbie; Meng, Shumei
Abstract : Published data regarding the approach to management of diabetes mellitus in solid organ transplant (SOT) recipients are limited. We performed a retrospective chart review of SOT recipients with diabetes, above 18 years of age, who were usisng dulaglutide. There was a sustained, statistically significant reduction in the primary endpoints of weight, body mass index (BMI) and insulin requirement in 63 SOT recipients at 6, 12 and 24 months, respectively. A total of 59, 50 and 13 recipients were followed during 6, 12 and 24 months, with a mean paired difference for weight reduction of 2.07 ( P value <0.003), 4.007 ( P value <0.001) and 5.23 ( P value <0.034) kgs and a BMI reduction of 0.80 ( P value <0.001), 1.35 ( P value <0.005) and 2.015 ( P value <0.045) kg/m 2, respectively. The mean paired difference for insulin reduction before and after dulaglutide treatment was 5.94 units ( P value <0.0002). There was no increased risk of malignancy, cardiovascular morbidity, graft‐failure or all‐cause mortality. Gastrointestinal manifestations were rare, even in patients with advanced chronic kidney disease (CKD), and required no change in immunosuppressive agents. Thus, dulaglutide may be considered an important option for diabetes management in SOT.